Feasibility and Thermal/Electrical performance study of two smart hybrid systems combining parabolic trough collector with tubular thermoelectric generator. (November 2021) - Habchi, A.; Hartiti, B.; Labrim, H.; Fadili, S.; Benyoussef, A.; Belouaggadia, N.; Faddouli, A.; Ertuğrul, M.; Benaissa, M.; Ntsoenzok, E.
Abstract: Hybrid parabolic trough concentrators were considered as the basis of co-generation systems, which mainly based on the Simultaneous production of thermal and electrical energy. In this paper, a thermal model of two cogeneration systems consisting parabolic trough collector, combined with a cylindrical thermoelectric generator was presented. The collector of the present configurations forms an annular channel between the inner side of absorber tube and upper surface of tubular thermoelectric generator. A heat transfer fluid (Therminol VP1 or hot water) is passed along the annular channel using a pump with low consumption, which mainly energized by the produced power from the tubular thermoelectric generator. Also, the heat transfer fluid (Therminol VP1 or Hot water) temperature is mainly based on the temperature adjustment principle, where the heat transfer fluid flow rate is adjusted according to sun irradiation to keep the heat transfer fluid temperature at 400 °C for Therminol VP1 or at 95 °C in the case of water. To examine the effects of solar concentration ratio and sun irradiation on the thermal and electrical performance of the hybrid system, a set of nonlinear equations were developed and coded in MATLAB software (R2015a). The power output and electrical efficiency of the tubular thermoelectric generator, the overall efficiency and net power as well as hot water storage of the hybrid systems were separately presented and discussed for all three solar concentration ratios and ten sun irradiation values. To validate the predicted results of the numerical model, two available research works have been used. The comparison of results obtained with results of the exact solution indicates a good agreement. The novel integration technique shows major improvements in thermal and electrical performance of both hybrid systems. As a results, the overall efficiency of the first hybrid system (Here, Therminol VP1 serves as a heat transfer fluid) reached to 70.550% corresponding to 306.5826 L/Day of Therminol VP1 at 400 °C and about 585 W of additional power. These values in the case of water serves as a heat transfer fluid up to 76.913%, 1058.467 L/D of hot water at 95 °C and 97.032 W of additional electrical power, respectively.